1996
DOI: 10.1046/j.1365-2141.1996.447982.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory factors associated with platelet transfusion refractoriness: a case–control study

Abstract: In recent years clinical factors have largely surpassed alloimmunization as the predominant cause of platelet refractoriness. This makes it necessary to properly identify and weigh the non-immune factors that have a major impact of refractoriness. A case-control study is suitable for such an analysis, and to our knowledge has not previously been performed to assess this issue. Fifty-two refractory patients were compared with 52 control patients who were transfused at the same time. Only one transfusion event w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
4

Year Published

1997
1997
2006
2006

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 13 publications
1
31
0
4
Order By: Relevance
“…This conclusion confirms previous data obtained in patient populations comprising transplanted and not-transplanted subjects. 9,24 However, different results were observed in the HSCT setting by Ishida et al, 4 who reported that antibodies to HLA-antigens had a relatively insignificant impact on 16-h CCI, while platelet-specific antibodies enhanced post-transfusion platelet efficacy. Since it is not possible to conciliate such opposite results, we are compelled to conclude that some confounding factor was unrecognized in one or other of the case series.…”
Section: Leukemiamentioning
confidence: 75%
See 1 more Smart Citation
“…This conclusion confirms previous data obtained in patient populations comprising transplanted and not-transplanted subjects. 9,24 However, different results were observed in the HSCT setting by Ishida et al, 4 who reported that antibodies to HLA-antigens had a relatively insignificant impact on 16-h CCI, while platelet-specific antibodies enhanced post-transfusion platelet efficacy. Since it is not possible to conciliate such opposite results, we are compelled to conclude that some confounding factor was unrecognized in one or other of the case series.…”
Section: Leukemiamentioning
confidence: 75%
“…In order to gain further information in this field, we performed a prospective study, evaluating a number of clinical and immune factors which potentially affect or have been previously shown to affect the efficacy of platelet transfusion, 4,5,[8][9][10][11][12][13] in a series of 87 consecutive children who received 598 platelet transfusions after allogeneic HSCT carried out in a single institution.…”
Section: Introductionmentioning
confidence: 99%
“…Durante mucho tiempo se han usado las transfusiones de plaquetas con fines profilácticos, para mantener el recuento de plaquetas por encima del nivel que se considera seguro (15,17). Sin embargo, y a pesar de su amplio uso, muchos estudios no han podido demostrar la eficacia de su administración profiláctica (5, 16).…”
Section: Concentrados De Varios Donantesunclassified
“…Se dice que un 20 a 60% de los pacientes no alcanzan los niveles deseados después de la transfusión y se consideran refractarios a la misma (17), fenómeno que se presenta como una complicación de su uso repetido (5). Sus causas incluyen la aloinmunización relacionada con antígenos plaquetarios y del sistema HLA, así como la autoinmunidad relacionada con otros antígenos, como ocurre en la púrpura trombocitopénica idiopática; en la refractariedad también se han implicado causas no inmunitarias, como la esplenomegalia, algunos medicamentos o la destrucción acelerada (4).…”
Section: Contraindicaciones Y Precaucionesunclassified
See 1 more Smart Citation